Mass diffusion over wind waves - Liu, Hsien Ta, author; Karaki, Susumu, author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1972)
The mass diffusion process from an elevated point source over a wind-disturbed water surface was investigated experimentally and numerically. The diffusion model which generated from this study was used also to compare experimental with calculated concentration distributions for diffusion in the boundary layer of a flat plate and over a mechanically-generated water wave. An optical device was developed to measure mean and fluctuating concentrations of small aerosol particles in the wind field. The frequency response and sampling volume of the optical device were found to be adequate for this study and comparable approximately to hose for a hot-wire anemometer. A steady stream of aerosol particles was generated by atomization of a heavy oil (Dioctyl Phthalate). Velocity measurements indicated that the flow conditions, that is, the normalized mean velocity U/U and relative turbulent intensities u'2/U and w'2/U were distributed similarly for flow over wind 00 00 waves for U  10 fps and over a flat plate for U  10 and 20 fps. Comparisons of normalized mean velocity distributions indicated that net momentum was transferred from the air stream to water waves and the amount transferred was proportional to the wind speed. However, there was less net momentum transfer from the air stream to mechanically-generated water waves. The relative turbulent intensities increased with increasing wind speed over wind waves. Comparatively large vertical gradients of u'2/U and w'2/U characterized the flow over mechanical waves. Results of concentration measurements indicated that the diffusion process is directly proportional to turbulent intensities. The in-fluences of turbulent diffusion, wind shear, and surface reflection resulted in shifting the maximum mean concentration toward the lower boundary while the turbulent diffusion shifted the maximum root-mean-square concentration upward and laterally. The mean concentration distributions over wind waves for U  10 fps were similar to those over a flat plate for U  20 fps. The comparatively large vertical 00 gradients of the relative turbulent intensities caused a large concentration accumulation at the mean water level over mechanical waves. Revised diffusivity models, based on those given by Hino (1968), are proposed. These models are dimensionally correct as opposed to the dimensionally incorrect Hino models and incorporate local conditions by introducing dependency on the boundary layer thickness. The diffusion equation was solved numerically, utilizing an improved finite-difference technique and by using measured flow conditions. The water surface was viewed, in the mean, as a flat surface with wave influences incorporated implicitly into the diffusivity models. With the net vertical mean velocity properly adjusted, general agreement was observed between numerical solutions and corresponding experimental data.
CER71-72HTL-SK46.
May 1972.
Prepared under contract no. AT(ll-1)-1813 Atomic Energy Commission Fallout Studies Branch.
Circulating copy deaccessioned 2020.
Keywords: Fluid mechanics; Channels (Hydraulic engineering)